(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Rivets are permanent, non-threaded, one-piece fasteners that join parts together by fitting through a pre-drilled hole and deformed the head by mechanically upsetting from one end. In this paper the results of experimental analysis based on lap-shear test on riveted connection are presented. For experimentation specimens were prepared and different thickness and configurations were considered. The results of experimental test allowed the influence of various parameters such as plate width and pitch. These results are compared with the Ansys result. The experimental test using Universal Testing Machine and shear stress results are calculated. These results were compared with model simulation in FEA software.